TELAAH KONSISTENSI AS-SUYUTHI DALAM MENILAI KUALITAS HADIS: STUDI ATAS KITAB AL-JAMI’ AL-SHAGHIR DAN LUBAB AL-HADITS - Ahmad Saerozi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
As-Suyuthi is one of the hafiz (memorized a hundred thousand hadiths along with their sanad and matan) who mastered seven discipline, namely: tafsir, hadis, fiqh, nahwu, ma’ani, bayan, and badi’. Among his works in hadith are Lubab al-Hadits and al-Jami’ alShagir. Both of those books are widely used as reference in the university and pesantren (school of Koranic for people). Jami’ al-Shaghir being used as reference to look for primary hadith resource caused by its characteristic using hadith indexed. These book allows people to look for hadith that they needed and arranged alphabetically from alif to ya’ by including hadith’s matan. The assessment method used by as-Suyuthi is by mention the hadith then provide information about the quality of the hadith. While, Lubab al-Hadits is a book of hadith which contains a collection of hadith that explain about ethics and the virtues of charity. The method to evaluate hadith used by al-Suyuti are explained in the muqaddimah (preface). It said that all hadith that have been mentioned are sahih, so the sanad was discarded. The purpose of this research is to determine the extent of consistenty of As-Suyuthi in evaluating the quality of hadith in his two books mentioned before accompanied by an example of application and also to find out what factors related to that. This research is a library research that investigate figure (people). The research conduct qualitatively by collecting data through documentation from primary and secondary resources and using inductive method. Result of the study show that: as-Suyuthi is not consistent on assessing the quality of the hadith in his two books, al-Jami’ al-Shaghir dan Lubab al-Hadits. This is due several factors, including: (1) the differences in assessment methods, (2) the difference of the time (year) when the book was written, and (3) the difference of social and educational settings that experienced by As-Suyuthi.